Characterizing Heart Rate Response During Upper Extremity Repetitive Task Practice in Chronic Stroke. - Davidson, Sara; Bischof-Bockbrader, Andrea; Zimmerman, Eric; Rosenfeldt, Anson B.; Alberts, Jay L.; Linder, Susan M. (American Journal of Occupational Therapy)
Importance: Although the cardiopulmonary benefits of aerobic exercise poststroke are well-established, typical stroke rehabilitation does not elicit an aerobic response. Objective: To characterize heart rate response during upper extremity repetitive task practice (RTP) and determine factors that predict a higher aerobic intensity during RTP. Design: Secondary analysis of a subset of data from a randomized clinical trial. Setting: Research laboratory in a large academic medical center. Participants: Patients with chronic stroke (N = 19). Intervention: Participants received 90 min of RTP for 24 sessions across 8 wk. Outcomes and Measures: Aerobic intensity as measured by heart rate reserve (HRR) during RTP. Results: A total of 2,968 tasks were included in the analysis. Of the tasks performed, approximately 79.5% elicited a very light aerobic response (<30% HRR), 10.2% elicited a light aerobic response (30%–39% HRR), and 10.3% elicited a moderate to vigorous intensity aerobic response (≥40% HRR). Of the tasks that elicited a moderate to vigorous intensity aerobic response, 54.1% were performed in standing, 79.7% were gross motor in nature, and 27.9% had targets at or above shoulder height. Standing position, targets at or above shoulder height, and gross motor tasks predicted higher HRR (all ps <.001). Conclusions and Relevance: To maximize aerobic intensity during poststroke RTP, therapists should include gross motor tasks trained in standing with targets at or above shoulder height. Plain-Language Summary: The study characterizes heart rate response in stroke rehabilitation and identifies factors that predict a higher aerobic intensity during upper extremity repetitive task practice. Certain task characteristics were more likely to produce an aerobic response, including gross motor, targets at or above the shoulder, and a standing position. Occupational therapists should include gross motor tasks trained in standing with targets at or above shoulder height to maximize aerobic intensity during poststroke repetitive task practice. Monitoring heart rate may improve awareness of aerobic response to training. The study findings show that occupational therapists should include gross motor tasks trained in standing with targets at or above shoulder height to maximize aerobic intensity during poststroke repetitive task practice.